1á,25(OH)2-VITAMIN D3 IN PROSTATE: INTERSECTION WITH AKT/PTEN AXIS AND ROLE IN SENESCENCE - Axanova, Linara (Wake Forest University, 2010)
The PI3K-AKT pathway is frequently activated in prostate cancer and can lead to downregulation of p21 and p27 levels and function. 1-alpha, 25-dihydroxy vitamin D3 (1á,25(OH)2D3) inhibits proliferation of multiple cancer cell types, including prostate cancer cells, and upregulates p21 and/or p27. We hypothesized that inhibition of the PI3K/AKT pathway would synergize with the antiproliferative signaling of 1á,25(OH)2D3. We found that pharmacological inhibitors of PI3K or AKT and 1á,25(OH)2D3 synergistically inhibit growth of DU145, LNCaP and primary human prostate cancer cells. Combination of 1á,25(OH)2D3 and an AKT inhibitor cooperated to induce G1 arrest, senescence and higher p21 levels in prostate cancer cells. As AKT activation in prostate cancer usually occurs due to the loss of tumor suppressor PTEN, we evaluated the effect of Pten loss on 1á,25(OH)2D3)-mediated antiproliferative effects utilizing mouse prostatic epithelial cells (MPEC) with acute in vitro Pten knockdown or knockout. We found that loss of Pten expression led to a partial induction of cellular senescence. Upon treatment with 1á,25(OH)2D)3, MPEC which had lost Pten showed significantly higher levels of growth inhibition and senescence induction compared to the Pten-expressing counterparts. In contrast to the MPEC with in vitro acute deletion of Pten, Pten null MPEC isolated from Pten-deletion-driven tumors showed a complete loss of sensitivity to 1á,25(OH)2D3 -mediated growth inhibition, which was partially restored by co-treatment with a PI3K or AKT inhibitor. Moreover, this combination led to synergistic growth inhibition of tumor-derived Pten null MPEC. These observations suggest that initial loss of Pten in prostate cells may result in an increased sensitivity to 1á,25(OH)2D3-mediated antiproliferative effects, possibly by additive effect on senescence induction; whereas subsequent changes associated with tumor progression may lead to abrogation of 1á,25(OH)2D3-sensitivity, which at least partially can be overcome by combination with PI3K/AKT inhibitors. We have also discovered a novel mechanism for the antiproliferative effects of 1á,25(OH)2D3- senescence. Together, these findings providing a rationale for further testing of therapeutic intervention using 1á,25(OH)2D3 for slowing the process of tumorigenesis of earlier pre-tumoral stages of prostate neoplastic disease as well for testing combinations of 1á,25(OH)2D3 with PI3K/AKT inhibitors for the treatment of prostate cancer.
Keywords: AKT; cancer; prostate; senescence; synergism; vitamin D